Penggunaan Media YouTube dalam Pengajaran Berbicara kepada Level Pemula - Ulum, Miftahul; Hamamah, Hamamah; Rohmah, Zuliati; Muttaqin, Syariful; Fadillah, Alifa (Hasta Wiyata, 2024)
This study explores the integration of YouTube videos as a teaching tool to enhance the speaking abilities of beginner-level students in English. Drawing upon the principles of multimodal learning and digital technology in language education, the research investigates the impact of utilizing YouTube videos on language learning outcomes. Adopting a qualitative descriptive design, the study examines English language learning activities conducted with the aid of YouTube videos at TPQ Raudlotus Shibyan, involving five students aged 13-14. Data collection methods include pre-activity preparations, engagement in main activities with listening and speaking exercises facilitated through YouTube videos, and post-activity feedback and assessment. Findings reveal that YouTube videos effectively stimulate student engagement, motivation, and comprehension of English speaking skills, fostering a dynamic and interactive learning environment. This research underscores the potential of digital technology, particularly YouTube, as a valuable resource for language educators seeking to create engaging and effective language learning experiences, especially for beginner-level students.